A survey of architectural techniques for DRAM power management. (1st January 2012) - Mittal, Sparsh
Recent trends of CMOS technology scaling and wide-spread use of multicore processors have dramatically increased the power consumption of main memory. It has been estimated that modern data-centres spend more than 30% of their total power consumption in main memory alone. This excessive power dissipation has created the problem of 'memory power wall' which has emerged as a major design constraint inhibiting further performance scaling. Recently, several techniques have been proposed to address this issue. The focus of this paper is to survey several architectural techniques designed for improving power efficiency of main memory systems, specifically DRAM systems. To help the reader in gaining insights into the similarities and differences between the techniques, this paper also presents a classification of the techniques on the basis of their characteristics. The aim of this paper is to equip the engineers and architects with knowledge of the state of the art DRAM power saving techniques and motivate them to design novel solutions for addressing the challenges presented by the memory power wall problem.